Design of an E × B Chopper System Based on Permanent Magnets for the Injection Line of the SPES Project Cyclotron - Alberto Ruzzon; Mario Maggiore; Arturo Abbondanza; Piergiorgio Antonini; Lorenzo Pranovi (Instruments, 2025)
This paper presents the requirements and design solutions of the chopper for the injection line of the cyclotron of the SPES project at Laboratori Nazionali di Legnaro. The device aims to precisely modulate the average current injected into the cyclotron, thereby controlling the current it delivers. A precise control of the beam current is essential for many experiments foreseen for the cyclotron. Due to safety constraints and limited space, a tailored design has been developed. The chopper features a Wien filter configuration, where the electric field is pulsed and the magnetic field is generated by permanent magnets.